Consensus Review of Best Practice of Transanal Irrigation in Children. Issue 3 (March 2017) - Mosiello, Giovanni; Marshall, David; Rolle, Udo; Crétolle, Célia; Santacruz, Bruno G.; Frischer, Jason; Benninga, Marc A.
Abstract : ABSTRACT: Pediatric patients with either functional or organic bowel dysfunction may suffer from constipation and fecal incontinence and represent a complex group in whom management is often difficult. Many noninvasive and invasive treatments have been proposed, with variable efficacy and adverse effects. Transanal irrigation (TAI) is now an accepted alternative, in both children and adults, for bowel dysfunction that has not responded to conservative and medical therapies. There is, however, still some uncertainty about the use of TAI in pediatric populations. Hence, a group of specialists from different nations and pediatric disciplines, all with long-standing experience of bowel management in children, performed a literature search and had round table discussions to determine the best-practice use of TAI in the pediatric patient population. Based on these findings, this article provides best-practice recommendations on indications, patient selection, important considerations before treatment, patient and family training, treatment regimens, troubleshooting, and practical aspects of TAI. We conclude that careful patient selection, a tailored approach, directly supervised training, and sustained follow-up are key to optimize outcomes with TAI in children with functional or organic bowel dysfunction. Abstract : Supplemental Digital Content is available in the text